UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL (CIRC) BERBANTUAN MEDIA KOMIK EDUKATIF PADA PESERTA DIDIK KELAS III SEKOLAH DASAR - Aulia Veronika Lizani; Destrinelli .; Silvina Noviyanti (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research aims to determine the process of implementing the Cooperative Integrated Reading and Composition (CIRC) Model Assisted by Educational Comic Media in improving the reading comprehension concept abilities of Class III Students at SDN 112/I Perumnas. This type of research is classroom action research. This research data was obtained from observation, tests and documentation. Then the data was analyzed qualitatively by describing the increase in students' reading comprehension skills using educational comic media and quantitatively in the form of students' reading test scores. Based on the results of research related to the application of the (CIRC) Model Assisted by Educational Comic Media, it is able to improve the concept of reading comprehension in students. In the first cycle it was discovered that the students' reading level was still low with a percentage reaching 44%, meaning that it had not reached the indicators expected in this research, and after improvements were made in the second cycle it increased with a percentage reaching 76%. From the results of this research, it can be concluded that the actions provided by implementing the Cooperative Integrated Reading and Composition (CIRC) model assisted by educational comic media were successful in improving students' reading comprehension skills.